Structure and status of the Italian red coral forests: What can a large-scale study tell? - Toma, Margherita; Bo, Marzia; Giudice, Daniele; Canese, Simonepietro; Cau, Alessandro; Andaloro, Franco; Angiolillo, Michela; Greco, Silvestro; Bavestrello, Giorgio (Frontiers in Marine Science, 2022)
The precious coral Corallium rubrum (Linnaeus, 1758) is a charismatic Mediterranean species. A recent large-scale investigation along the Italian coast highlighted its widespread occurrence at mesophotic and upper bathyal depths, especially on coralligenous and bathyal vertical hardgrounds. The lack of morphometric data limited the considerations on the structure and health status of the populations, fundamental to identify the most vulnerable sites and the correct management actions. For this reason, a ROV dataset, consisting of 624 dives carried out between 40 m and 1825 m in the Ligurian Sea, Tyrrhenian Sea, and Sicily Channel, was analysed to extrapolate quantitative data to describe the populations. Ten random frames were obtained from each of the 170 sites hosting red coral. Density, height, and entanglement were evaluated for about 15700 colonies counted in the frames. The densest populations were mainly found between 40 m and 80 m, with a clear latitudinal density decrease. The mesophotic populations were characterized by both scattered and densely aggregated colonies, while the bathyal ones were dominated by sparse colonies. This study identified 17 major coral areas based on the geographic proximity of the sites hosting red coral and their topographic and oceanographic affinity. The size-frequency distribution of the heights was skewed towards the smaller classes in almost all populations, with a modal class between 2 cm and 4 cm. This study depicted a stress situation of the populations throughout the entire study area, which could be correlated also to the long-term harvesting pressure carried out in the basins. Two additional sources of direct mortality were pointed out in this study. Entanglement to artisanal and recreational fishing gear interested about 18% of the recorded colonies, mainly at mesophotic depths. Almost all populations suffered from mechanical entanglement, with the highest percentages in the Ligurian Sea and Sicilian areas. This study also highlighted a massive occurrence of recent deep mortality events, mainly along the eastern and southern coast of Sardinia and in the Campanian Archipelago. Thirty sites with extensive patches of dead colonies still in place were reported from 70 m to around 200 m, but their formation remains unclear.